The Ecopopulism Movement of the Samin Community against Cement Companies in The Kendeng Mountains - Enkin Asrawijaya (Jurnal Sosiologi Pendidikan Humanis, 2020)
The focus of this study is on the movement of the Samin group (indigenous people) in Bombong Hamlet, Sukolilo, Pati, Central Java, who are able to mobilize the masses, especially Kendeng farmers to oppose the establishment of a cement factory in the Kendeng mountainous area, because if a cement factory is established. will damage the environment which also has an impact on the local economy, especially the disruption of the profession of farmers due to loss of agricultural land and damage to springs that have supported them for their daily needs and to fertilize agriculture and feed and drink livestock. The theory and paradigm used in the discussion this time is to use the concept of ecopopulism, which is a social movement that focuses more on environmental sustainability because in it there is local livelihood which has been the mainstay of society, one of which is agriculture. so that this movement seeks to maintain the position of natural resources in the hands of local communities. The research method used was observation and in-depth interviews with Samin Bombong community leaders and there were also elements from Kendeng farmers. The results showed that there were three things that became the main focus of the birth of the ecopopulism movement, namely environmental, economic and legal factors. These three things form a movement ideology, namely ecopopulism, which has been able to attract many masses, especially Kendeng farmers, which eventually formed a movement organization, has a wide network, and resistance is open. Fokus penelitian ini adalah pada gerakan komunitas Samin di Dusun Bombong, Pati, Jawa Tengah, yang mampu melakukan mobilisasi massa, terutama petani Kendeng untuk melawan pendirian pabrik semen di area pegunungan Kendeng, hal tersebut karena adanya kekhawatiran jika pendirian pabrik semen terlaksana maka akan merusak lingkungan yang berimbas pula pada perekonomian lokal, khususnya terganggunya profesi petani. Teori yang digunakan dalam pembahasan kali ini adalah menggunakan konsep ekopopulisme, yaitu sebuah gerakan sosial yang lebih menitik beratkan kepada kelestarian lingkungan karena di dalamnya terdapat penghidupan lokal yang selama ini menjadi andalan masyarakat, salah satunya pertanian, sehingga gerakan ini berupaya mempertahankan kedudukan sumber daya alam tetap berada di tangan masyarakat lokal. Metode penelitian yang digunakan adalah etnografi. Hasil penelitian menunjukan bahwa Ada tiga hal yang menjadi sorotan utama lahirnya gerakan ekopopulisme, yaitu faktor lingkungan, ekonomi dan hukum. Ketiga hal inilah yang membentuk sebuah ideologi gerakan yaitu ekopopulisme, yang telah mampu menarik banyak massa terutama petani Kendeng yang pada akhirnya terbentuklah organisasi gerakan, memiliki jejaring yang luas, dan perlawananpun terbuka.